The Controlled Economy, its Legal Basis and Criminal Protection in the Protectorate of Bohemia and Moravia (1939 – 1945) - Jaromír Tauchen (Journal on European History of Law, 2023)
Immediately after the establishment of the Protectorate of Bohemia and Moravia, the government of the Protectorate began to enact legislation for the transition to a controlled economy, following the Reich model. Its nature varied, but at least two basic groups can be distinguished: legislation regulating the market and legislation regulating the rationing system. One of the main features controlled economy of the Protectorate was the freezing and control of prices, for which the Supreme Price Office was created. In practice, restrictions on the free sale of food, fuel and other commodities played a crucial role. At the same time, Czech-Moravian associations were created – they managed and controlled the production and distribution of food and other commodities, and some state functions were delegated to them. In course of the implementation of the controlled economy, essential management and control tasks were also delegated to the provincial and district authorities, which also prosecuted offences against maintenance economy and controlled economy. In the course of time, repression took hold, and the German special courts punished with all the vigour and severity they could, even in the case of Protectorate citizens, acts against economic regulations.